Analisis Kesulitan Belajar Siswa Kelas XI MAN 1 Lombok Tengah Pada Mata Pelajaran Kimia - Citra Hijrathaen; Lalu Rudyat Telly Savalas; Sunniarti Ariani (FKIP University of Mataram, 2025)
Learning difficulties are obstacles that hinder students from achieving optimal academic performance. This study aims to analyze the learning difficulties encountered by Grade XI students in chemistry and to identify the contributing factors. The research employed a descriptive method with a qualitative approach, involving 70 students from MAN 1 Central Lombok as research subjects. Data were collected using questionnaires, interview guides, and students’ test scores. The research instruments were validated by three expert validators, yielding a validity score of 0.88, indicating a high level of validity, and tested for reliability using Cronbach’s Alpha, which confirmed their consistency. Data were analyzed descriptively by calculating the percentage of learning difficulties based on specific indicators or criteria. The findings revealed that students faced major difficulties in calculation-based materials (60%) and theoretical concepts (54.06%). Interviews were conducted to strengthen the data obtained from the questionnaires. The contributing factors were categorized into internal factors, external factors, and learning approaches, with internal factors being the most dominant at 59%. This study is expected to serve as an evaluation material for teachers and schools in designing more effective and context-based learning strategies in chemistry education.